Does the clinical assessment help in predicting malignancy in thyroid swell - Devkota, Ishwor Raj; Bhandary, S.; Karki, S. (Nepalese Journal of ENT Head and Neck Surgery, 2017)
Objectives: To predict malignant nodules in solitary thyroid nodules on clinical assessment.Materials and methods: A total of 48 cases with thyroid nodule were clinically assessed in detail and underwent the standard thyroid surgery at BPKIHS, Dharan during the period of one year (April 2012 to march 2013).Results: The mean age was 41.42 years with female to male ratio of 15:1. Most of the patients were euthyroid (73%). Majority of the thyroid nodules were malignant (85.4%) and only 14.6% were benign on clinical assessment. The sensitivity of clinical evaluation was 84.6%, specificity 13.6%, positive predictive value 53.6%, negative predictive value 42.8%. Percentage of the false negative, false positive and overall accuracy was 57.1%, 46.3% and 52% respectively.Conclusion: Even though the sensitivity is high, clinical assessment has low specificity. So we cannot rely on clinical assessment in predicting malignancy in the thyroid nodules.